2017
DOI: 10.1161/strokeaha.117.018450
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Cationic Protein, Carotid Plaque, and Incidence of Stroke

Abstract: High ECP is associated with increased incidence of IS. The association between ECP and IS was also present in the subgroup with carotid plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
0
20
0
2
Order By: Relevance
“…17,18 Elevated plasma concentrations of ECP have been associated with increased incidence of ischemic stroke. 19 In patients with systemic lupus erythematosus and lupus nephritis, urine ECP/UCr ratio has been found to have better correlation with renal function and SLE disease activity, compared to urine interleukin-5 (IL-5/UCr ratio). 20 In the current study, we observed that urine ECP/UCr was significantly associated with blood eosinophil counts, systemic inflammation, glomerular lesions, and the average number of cortex infiltrated eosinophils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Elevated plasma concentrations of ECP have been associated with increased incidence of ischemic stroke. 19 In patients with systemic lupus erythematosus and lupus nephritis, urine ECP/UCr ratio has been found to have better correlation with renal function and SLE disease activity, compared to urine interleukin-5 (IL-5/UCr ratio). 20 In the current study, we observed that urine ECP/UCr was significantly associated with blood eosinophil counts, systemic inflammation, glomerular lesions, and the average number of cortex infiltrated eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ECP can be used as a marker for estimating eosinophil inflammatory activity in asthma and other inflammatory diseases, and its levels are related to disease severity 17,18 . Elevated plasma concentrations of ECP have been associated with increased incidence of ischemic stroke 19 . In patients with systemic lupus erythematosus and lupus nephritis, urine ECP/UCr ratio has been found to have better correlation with renal function and SLE disease activity, compared to urine interleukin‐5 (IL‐5/UCr ratio) 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophil granule proteins, including eosinophil cationic protein, eosinophil peroxidase, and major basic protein can cause cytotoxic protein-mediated thrombosis and endothelial injury 30 . ECP also stimulates broblast migration and brosis, which could be play an important role in the development of atherosclerosis [31][32][33][34] . It could be speculated that increased ECP and activated eosinophils were associated with increased incidence of AIS through effects on unstable plaque.…”
Section: Discussionmentioning
confidence: 99%
“…And, 3-activated eosinophils have prothrombotic functions. 7 Eosinophils is many-sided leukocytes that contributes to many pathological and physiological processes related to CVD risk. The contribution of eosinophils in CVD risk depend on the activation status and on the location of the eosinophils.…”
Section: Reply From the Authormentioning
confidence: 99%